Smart Parking Reservation System - Bonashi, Ashwaq (2021)
Due to the significant increase in the usage of vehicles, finding a parking spot has become a critical issue to car drivers. The parking spot problem can be daily faced in public places or even at workplaces. In some countries, such as Kuwait, it is usually hard to know the availability of a spot in a parking lot. For instance, almost all parking lots in Kuwait, including those at the hospitals and shopping malls, run in traditional way in which drivers enter the parking lot and start looking for an empty spot. Besides, some people tend to park near the sidewalk which can be disturbing to other drivers and results in parking limitation. The situation gets worst during rush hours. The aim of this project is to design a smart parking reservation system based on Internet of Things (IoT) technology in order to mitigate this problem. The parking lot will be equipped by smart gates that will operate using solar panel. The solar panel will provide clean energy to the whole floor. The advantage of relaying on renewable energy is to reduce the power outage that can stand as a barrier in many countries. Drivers will use the application to check the availability of a parking spot, enter the parking lot, open the gate of their reserved spot, and pay. Moreover, only those who reserved a parking spot can enter the main parking lot gate, otherwise it will prevent other cars from entering. The vision behind constructing a modern parking lot is to refine the infrastructure, reduce parking congestion, and save time. As an initial step, the project will be conducted on one floor. However, high standard civilization can be acquired by enlarging the floor scale to smart buildings and cities